Kontribusi Aspek Anthropometri dan Kapasitas Fisik Dominan Terhadap Prestasi Lompat Jauh Gaya Schenepper - Amiruddin, Prima Setia (Jurnal Simki Postgraduate, 2023)
The long jump is an athletic sport with a series of prefixes, pedestals, attitudes in the air, and ends with a landing which includes power and speed with the aim of jumping with the achievement of the farthest jump distance. Based on the formulation of the problem that has been stated above, the objectives to be achieved in this study are to: 1) Find out how much the body mass index factor contributes to the schenepper style long jump achievement. 2) Knowing how much the leg muscle power factor contributes to schenepper style long jump performance. 3) Knowing how much the abdominal muscle strength factor contributes to schenepper style long jump performance. 4) Knowing how much the contribution of the maximum running speed factor to schenepper style long jump achievement. In this case, what will be examined is the contribution of anthropometric aspects and dominant physical capacity to the schenepper style long jump achievement of grade 8 male students of SMP Negeri 2 Karangrejo, Tulungagung Regency. Where the researcher seeks to find the most effective alternative contribution to get schenepper style long jump achievement results with a descriptive quantitative multivariate correlation research design correlation which has 4 independent variables, namely anthropometric aspects (body mass index) (x1), and physical domain capacity including muscle power legs (x2), abdominal muscle strength (x3), maximum running speed (x4), and 1 dependent variable, namely schenepper style long jump performance (y). The object of this study was the schenepper style long jump learning outcomes, with a population of 150 students, the results of 30 students were taken randomly. In this study, the data analysis used was multiple regression analysis. Based on the results of the study it can be seen that there is a significant contribution in the anthropometric aspect (body mass index) to the Schenepper style long jump achievement of 15.4%. There is a significant contribution of physical dominance (leg muscle power) to schenepper style long jump achievement of 11.1%. There is a significant contribution to dominant physical capacity (abdominal muscle strength) to the Schenepper style long jump achievement of 7.6%. There is a significant contribution of dominant physical capacity (maximum running speed) to the Schenepper style long jump achievement of 14.7%. Based on some of the results above, it can be concluded that anthropometric aspects and dominant physical capacity contributed 48.8% to the Schenepper style long jump achievement.